A Large, First-Year, Introductory, Multi-Sectional Biological Concepts of Health Course Designed to Develop Skills and Enhance Deeper Learning - Murrant, Coral L; Richardson, Nicolette S; Dyck, David J; Kirkland, James B; Newton, Genevieve S; Ritchie, Kerry L; Tishinsky, Justine M; Bettger, William J (Canadian Journal of Higher Education, 2015)
Large first-year biology classes, with their heavy emphasis on factual content, contribute to low student engagement and misrepresent the dynamic, interdisciplinary nature of biological science. We sought to redesign a course to deliver fundamental biology curriculum through the study of health, promote skills development, and encourage a deeper level of learning for a large, multi-section first-year class. We describe the Biological Concepts of Health course designed to encourage higher-order learning and teach oral communication and independent learning skills to large numbers of first-year students. We used the Blooming Biology Tool to determine the cognitive skills level assessed in the newly developed course and the courses it replaced. This evidence-based approach demonstrated that our new course design achieved the goal of encouraging a deeper level of cognition, and further, successfully introduced both oral communication and independent learning skills in large first-year classes.